Interprofessional Collaboration Practices in Integrated ANC Services: Scoping Review - Yohana Samosir; Sulistyaningsih Sulistyaningsih (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Obstetric complications often occur in pregnant women because not all pregnant women regularly make integrated ANC visits, causing problems of maternal mortality that never go away. This research aims to examine interprofessional collaboration practices in integrated ANC services. The method used is Scoping Review as a research design. A scoping review is a precursor to a systematic review, aiming to identify the types of evidence available about the topic under discussion. They are using the PRISMA-ScR framework by searching for articles through relevant databases. Research results: Based on a search of 1,534 selected papers, ten essays met the inclusion criteria, and of the ten articles reviewed, it was found that the role of interprofessional collaborative practice among various health workers had not carried out their duties based on the responsibilities of each profession and the development and empowerment of human resources. Obstacles were found in supporting facilities, skills, awareness, and communication by Health workers to be overcome to obtain integrated ANC services to increase visits and obtain quality pregnancy checks, thereby reducing cases of maternal and neonatal deaths.